Psychometric Properties of Lower Extremity Strength Measurements Recorded in Community Settings in Independent Living Older Adults. Issue 3 (27th May 2019) - Alqahtani, Bader A.; Sparto, Patrick J.; Whitney, Susan L.; Greenspan, Susan L.; Perera, Subashan; Brach, Jennifer S.
ABSTRACT: Background : A uniaxial load cell device provides an alternative, easy and inexpensive way to quantify muscle strength in different settings outside the clinic and research labs. So, the purpose of the study was to examine the test–retest reliability and the construct validity of lower extremity strength performance using an uniaxial load cell device. Methods : A total of 131 subjects (85% female, mean age 80 ± 8 years) were included for the validity aim, and a sample of 38 subjects were enrolled in the reliability testing (89% female, mean age 76 ± 7 years). For the strength measurements were assessed with a portable load cell for three consecutive trials. Test–retest reliability was assessed over two testing visits occurring one week apart. Spearman's rank correlation coefficient was used to test convergent validity with other mobility-related measurements construct validity at baseline. Results : Strength measurements showed good to excellent reliability in most of the measured parameters with intraclass correlation coefficients range from 0.89 to 0.99 and were correlated with mobility measurements with Spearman rho range from 0.21 to 0.38. Conclusion : The portable uni-axial load cell to measure lower extremity strength provides reliable measurements in community settings.